Development and characterization of crab-based chitosan filler–reinforced polymer composites - Mohd Saiful, Asmal Rani; Ahmad Salihin, Samsudin; Mohd Nor Faiz, Norrrahim; N.M., Nurazzi; Muhammad Khalis, Abdul Karim; Mohd Hafiz, Mohd Zaid; Muhammad Kashfi, Shabdin; Mohd Mustafa, Awang Kechik; Khalina, Abdan (Elsevier Ltd, 2024)
New developments require innovative eco-friendly materials defined by their biocompatibility, biodegradability, and versatility. For that reason, the scientific society is focused on biopolymers such as chitosan, which is the second most abundant in the world after cellulose. Chitosan was extracted from crab excrement, a cheap and plentiful source, and added to a polymer matrix to improve mechanical and thermal characteristics. Chitosan was created by chemically deproteinizing and demineralizing crab shells. Chitosan filler was combined with a polymer matrix via solvent casting to form composite films. The addition of chitosan filler into the polymer matrix has improved the mechanical performance. The thermal characteristics of the composite, which were examined using thermogravimetric analysis, proved that chitosan filler increased the thermal stability. Chitosan filler–polymer matrix interaction and the composite’s microstructure were both investigated using scanning electron microscopy. Chitosan particles were evenly distributed throughout the polymer matrix, boosting interfacial bonding and reinforcing effects. A crab-based chitosan filler–reinforced polymer composite that was developed and studied showed promise as a sustainable substitute for materials used in various applications. Research may be used to improve the composite formulation and examine the biodegradability and long-term stability of the material.